Effect of Etomidate Used as Induction Drug for Emergency Intubation on Post Intubation Hypotension in Elderly Patients - Tantibundit, Porntipa (Srinagarind Medical Journal, 2024)
Background and Objective: Emergency tracheal intubation is a common lifesaving treatment in the emergency department, rapid sequence intubation is the standard method for performing this procedure. Etomidate is an induction drug which is commonly used due to minimal hemodynamic disturbance and having a short duration; however, the evidence of adverse effects in elderly patients are limit. The objective of this study was to evaluate the effect of etomidate used as induction drug for emergency intubation in elderly patients and post intubation hypotension. Methods: This was a retrospective study in elderly patients who were intubated in the emergency department. The enrolled patients were divided into etomidate used group and non-etomidate used group according to induction drugs used for intubation. The primary outcome was post intubation hypotension and secondary outcomes included the initiation or increased doses of vasopressors within 24 hours, the initiation of hydrocortisone within 24 hours and in hospital mortality. Results: A total of 231 elderly patients were enrolled in this study, 118 patients were in etomidate used group and 113 patients were in non-etomidate used group. In etomidate used group, 29 patients developed post intubation hypotension and 18 patients in non-etomidate used group experienced post intubation hypotension. Multivariable logistic regression showed no statistically significant association of etomidate used and post intubation hypotension in elderly patients adjusted odds ratio (AOR) 2.10 (0.94-2.71) p=0.070. However, etomidate was associated with the initiation or increased doses of vasopressors within 24 hours, the initiation of hydrocortisone within 24 hours and in hospital mortality. Conclusions: The study demonstrated that etomidate used was not significantly associated with post intubation hypotension but significantly associated with initiation or increased doses of vasopressors within 24 hours, initiation of hydrocortisone within 24 hours and in hospital mortality in elderly patients.